ANALISIS LAJU ALIR SAMPAH DAN EMISI CARBON YANG DIHASILKAN KOTA BANDA ACEH - M. Faisal (Jurnal Teknik Kimia USU, 2014)
This research aims to analyze the material flow of solid waste of Banda Aceh city by using Material Flow Analysis (MFA) method. The domestic wastes used in this research are limited to organic waste, plastic and paper. Results show that the solid wastes in Banda Aceh city do not treated well and thus required further treatment process. Wastes are separated at the kampong Jawa waste treatment process. Leaves waste are treated for compost, while no treatment process for plastic and paper wastes. The percentage of organic wastes, paper and plastic produced from Banda Aceh city were 89,1 %; 2,5 %; 0,74 %, respectively. Total amount of waste in the city of Banda Aceh is 86057,64 t/month producing carbon emission of 83726,6 t/month.